EFFECT of DIFFERENT SOLID AMOUNTS IN THE PHYSICAL and MICROSCOPICAL PROPERTIES of SiC POROUS CERAMICS - Santana, Jerusa G. A. [UNESP]; Minatti, Jose L.; de Campos, Elson; Melo, Francisco C. L.; Kajita, Tetunori (Trans Tech Publications Ltd, 2008)
The presence of pores in ceramics is directly related to the chosen forming process. So, in the starch consolidation method, the ceramics show, after burning, pores with morphology similar to that presented by this organic material. on the other hand, the increase in solid load leads up to alterations in dispersion viscosity, increasing the thermal stresses during drying and sintering processes. In order to verify the solid percentage influence in ceramic final properties, samples were prepared with silicon carbide in different compositions using or not starch as binder agent and pore forming element. The characterization of the ceramic pieces was performed by superficial roughness measurements, porosity besides by optical and scanning electron microscopy. The results showed ceramics with SiC and starch presented physical and microscopic properties slightly higher in relation to those with only ceramic powder in their composition. The presence of organic material, agglomerated and foam during the forming were essential for the final properties of the studied samples.
Keywords: ceramic; forming; Starch; porous; solid amounts